Using Intuitionistic Fuzzy TOPSIS in Site Selection of Wind Power Plants in Turkey - Babak Daneshvar Rouyendegh; Abdullah Yildizbasi; Ümmühan Z. B. Arikan (Advances in Fuzzy Systems)
The reduction of energy resources and the increase in environmental consciousness have recently increased the interest in renewable energy sources. Wind energy is from renewable energy sources, which are used in many countries. Turkey has a lot alternative wind energy plants thanks to its favorable geographical location. Where the wind power plant is to be established is a complex and important decisive factor. It is very important to select the appropriate wind power plant site to take advantage of wind energy and reduce costs. In this study, we aimed to reach the solution of wind energy plant site selection. For this purpose 4 alternative wind power plant locations have been identified. To evaluate the alternatives, 10 criteria in four dimensions including wind potential, location, cost, and social benefits are selected. Since the Multicriterion Decision Making (MCDM) methods are often used in problem of location selection from past to present, TOPSIS method combined with intuitionistic fuzzy set (IFS) has been used to achieve this goal. The main purpose of the TOPSIS method is to rank the alternatives in the worst way. The IFS are used to reflect approval, rejection, and hesitation of decision makers by dealing with real life uncertainty, imprecision, vagueness, and linguistic human decisions. Finally, a numerical example is applied for wind power plant site selection. In order to demonstrate the effectiveness of IFS, the problem is solved by the Fuzzy TOPSIS method using the same data. Then, the obtained results are compared with the IFS method to show the effectiveness of the proposed method.